Positively charged residues at the N-terminal arm of the homeodomain are required for efficient DNA binding by homeodomain-leucine zipper proteins - Palena, Claudia (2001)
Plant homeodomain-leucine zipper proteins, unlike most animal homeodomains, bind DNA efficiently only as dimers. In the present work, we report that the deletion of the homeodomain N-terminal arm (first nine residues) of the homeodomain-leucine zipper protein Hahb-4 dramatically affects its DNA-binding affinity, causing a 70-fold increase in dissociation constant. The addition of the N-terminal arm of Drosophila Antennapedia to the truncated form restores the DNA-binding affinity of dimers to values similar to those of the native form. However, the Antennapedia N-terminal arm is not able to confer increased binding affinity to monomers of Hahb-4 lacking the leucine zipper motif, indicating that the inefficient binding of monomers must be due to structural differences in other parts of the molecule. The construction of proteins with modifications at residues 5 to 7 of the homeodomain suggests strongly that positively charged amino acids at these positions play essential roles in determining the DNA-binding affinity. However, the effect of mutations at positions 6 and 7 can be counteracted by introducing a stretch of positively charged residues at positions 1 to 3 of the homeodomain. Sequence comparisons indicate that all homeodomain-leucine zipper proteins might use contacts of the N-terminal arm with DNA for efficient binding. The occurrence of a homeodomain with a DNA-interacting N-terminal arm must then be an ancient acquisition in evolution, earlier than the separation of lines leading to metazoa, fungi and plants.